Perilaku Etis Mahasiswa dan Dosen Ditinjau Dari Faktor Individual Gender dan Locus ff Control (Studi Empiris Pada Fakultas Ekonomi Universitas X di Jatim) - Hastuti, Sri (Jurnal Riset Ekonomi dan Bisnis, 2007)
College are produced of professional human resource who have qualification  according to its science area and ethical behavior expected can fulfill requirement of market. Target of this research to analyze difference of ethical behavior lecturer and student evaluated from gender individual factor and locus of control. Also prove ethical behavioral relation between lecturer and student Research population are student which have gone through more than 120 SKS, questioner propagated 262 exemplar, return 262 exemplar and can be processed 223. While lecturer disseminated 109 exemplar, return 56 exemplar and can be processed 44. Examination of conducted data quality that is validity test, reliability, and normality, while hypothesis test for first Hypothesis, second, fifth to sixth and also use test of one - Way Anova, and  fourth and third hypothesis used correlation test ( Pearson and of Partial Correlation)Result of this research : 1) there are difference of ethical behavior between men student with woman student. 2)no difference of ethical behavior between man dan woman lecturer Faculty of Economics University X. 3) there are positive relation between ethical behavior of lecturer with student. 4) there are interaction of gender to relation between ethical behavior lecturer with student 5) there are difference of ethical behavior between student of LOC internal with LOC eksternal 6) there are difference of ethical behavior between lecturer with internal LOC and lecturer with LOC eksternal.Keywords : Ethical Behavior, Gender, Locus of Control